2019
DOI: 10.1111/acel.12992
|View full text |Cite
|
Sign up to set email alerts
|

Early‐onset aging and mitochondrial defects associated with loss of histone acetyltransferase 1 (Hat1)

Abstract: Histone acetyltransferase 1 (Hat1) is responsible for the acetylation of newly synthesized histone H4 on lysines 5 and 12 during the process of chromatin assembly. To understand the broader biological role of Hat1, we have generated a conditional mouse knockout model of this enzyme. We previously reported that Hat1 is required for viability and important for mammalian development and genome stability. In this study, we show that haploinsufficiency of Hat1 results in a significant decrease in lifespan. Defects … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
33
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(33 citation statements)
references
References 67 publications
0
33
0
Order By: Relevance
“…It was shown that haploinsufficiency of Hat1leads to a significantly reduced lifespan of mice [88]. Premature aging was seen in Hat1 +/mice, demonstrated by phenotypes such as early lordokyphosis (hunchback), muscle atrophy, 4 Oxidative Medicine and Cellular Longevity minor growth retardation, reduced subcutaneous fat, cancer, and paralysis [88]. Kujoth et al generated mutant mice with impaired proofreading activity of DNA-polymerase γ and measured H 2 O 2 production in heart and liver mitochondria of young and old (3 months versus 9 months) mutant and wild-type mice.…”
Section: Increased Ros Productionmentioning
confidence: 99%
See 2 more Smart Citations
“…It was shown that haploinsufficiency of Hat1leads to a significantly reduced lifespan of mice [88]. Premature aging was seen in Hat1 +/mice, demonstrated by phenotypes such as early lordokyphosis (hunchback), muscle atrophy, 4 Oxidative Medicine and Cellular Longevity minor growth retardation, reduced subcutaneous fat, cancer, and paralysis [88]. Kujoth et al generated mutant mice with impaired proofreading activity of DNA-polymerase γ and measured H 2 O 2 production in heart and liver mitochondria of young and old (3 months versus 9 months) mutant and wild-type mice.…”
Section: Increased Ros Productionmentioning
confidence: 99%
“…Furthermore, rats treated with rotenone, an inhibitor of complex I activity, showed increased levels of ROS production and damage to brain mitochondria [ 87 ]. Significantly increased ROS levels were also detected in mouse embryonic fibroblasts (MEFs) heterozygous for a null mutation of histone acetyltransferase 1 (Hat1 +/- ) [ 88 ]. The increased ROS might be the consequence of mitochondrial dysfunction, since Hat1, which is responsible for the acetylation of newly synthesized histone H4 on lysine 5 and 12 during chromatin assembly, affects mitochondrial function through the acetylation of mitochondrial protein and the acetylation status of mitochondrial proteins can be a key regulator of protein function [ 88 ].…”
Section: Role Of Mitochondria In the Aging Processmentioning
confidence: 99%
See 1 more Smart Citation
“…Strikingly, Hat1 +/mice have a significantly shortened lifespan of approximately 69 weeks compared to greater than 120 weeks for wild type animals. A direct role for Hat1 in the normal aging process is suggested by the observation that Hat1 expression, at both the mRNA and protein levels, decreases dramatically with age in wild type animals [15]. Although they have opposite effects on protein acetylation, it is intriguing that decreases in Hat1 activity have a similar effect on aging as decreases in Sirtuin activity.…”
Section: Hat1mentioning
confidence: 99%
“…The mechanism(s) by which Hat1 influences aging are not clear as Hat1 is involved in multiple cellular process important to aging at the cellular level. These include transcriptional regulation, DNA damage repair, genome stability and mitochondrial function [14,15,[17][18][19][20][21]. In addition, a recent proteomic analysis indicates that Hat1 influences the acetylation state of a number of proteins known to be important for mammalian aging (Agudelo Garcia,et al, bioRxiv doi: https://doi.org/10.1101/825539).…”
Section: Hat1mentioning
confidence: 99%